Musical playschool activities are linked to faster auditory development during preschool-age: a longitudinal ERP study - Putkinen V; Tervaniemi M; Huotilainen M (NATURE PUBLISHING GROUP, 2025)
The influence of musical experience on brain development has been mostly studied in school-aged children with formal musical training while little is known about the possible effects of less formal musical activities typical for preschool-aged children (e.g., before the age of seven). In the current study, we investigated whether the amount of musical group activities is reflected in the maturation of neural sound discrimination from toddler to preschool-age. Specifically, we recorded event-related potentials longitudinally (84 recordings from 33 children) in a mismatch negativity (MMN) paradigm to different musically relevant sound changes at ages 2-3, 4-5 and 6-7 years from children who attended a musical playschool throughout the follow-up period and children with shorter attendance to the same playschool. In the first group, we found a gradual positive to negative shift in the polarities of the mismatch responses while the latter group showed little evidence of age-related changes in neural sound discrimination. The current study indicates that the maturation of sound encoding indexed by the MMN may be more protracted than once thought and provides first longitudinal evidence that even quite informal musical group activities facilitate the development of neural sound discrimination during early childhood.